Decentralised autonomous organisation (DAO) regulation : principles and perspectives for the future - International Conference on DAO Regulation; Perestrelo de Oliveira, Madalena; Garcia Rolo, Anónio (Mohr Siebeck, 2024)
The Lisbon Centre for Research in Private Law (CIDP)'s research project Lisbon DAO Observatory is on a mission to find answers to the questions regarding the legal challenges and the current legal state of decentralised autonomous organisations (DAOs) and similar arrangements that will help shape future legislative action. In April 2023, the project held an international conference on DAO regulation that gathered top-tier scholars, industry players and practitioners from all over the world to discuss how any prospective legislative intervention, recognition or regulation of DAOs should be crafted. This volume is the result of the knowledge shared and gained during this ground-breaking conference and includes discussions on the future form of regulation (direct legislative intervention, self-regulation or no regulation) as well as on major topics such as mandatory decentralisation, legal personality, governance structures, limited liability, plus crucial sectorial issues, including dispute resolution, civil liability, tax law and conflict of laws.